Perception and Quality of Breakfast on Primary School Children - Atika Putri Indrasari; M. Mutalazimah; Dewi Kumalasari; Ajeng Puspa Buana (Journal of Nutraceuticals and Herbal Medicine, 2018)
Introduction: The determination of nutrition in breakfast is done by observing the quality of breakfast, such as the variety of food and the energy intake. One of the factors that influence the quality of breakfast is perception. Based on the results of preliminary survey, approximately 65% of students less understand about the importance of breakfast. Objective: This study aimed to determine the relationship between perception and the quality of breakfast, including food variety and energy intake, on primary school children at Madrasah Ibtida’iyah Muhammadiyah (MIM) Innovative Gonilan Kartasura. Methods: It is an observational study with cross sectional approach and sample size of 57 children were selected by simple random sampling. Perception was measured using a Likert scale questionnaire, the variety of food was measured using a questionnaire of food variation and the assessment of energy intake was done through interview using a 24-hour food recall form, then analyzed by Pearson product moment correlation test and Spearman rank test. Results: The perception of breakfast was considered adequate by 66.7%,the variety of food was classified as less by 50.9% and energy intake was considered more by 93%. Conclusion: there is no correlation between perceptions of breakfast and variety of food (p= 0,651) and energy intake (p= 0,696).